Rethinking Extinction - Dunsmoor, Joseph E; Niv, Yael; Daw, Nathaniel; Phelps, Elizabeth A (Neuron (Cambridge, Mass.), 2015)
Extinction serves as the leading theoretical framework and experimental model to describe how learned behaviors diminish through absence of anticipated reinforcement. In the past decade, extinction has moved beyond the realm of associative learning theory and behavioral experimentation in animals and has become a topic of considerable interest in the neuroscience of learning, memory, and emotion. Here, we review research and theories of extinction, both as a learning process and as a behavioral technique, and consider whether traditional understandings warrant a re-examination. We discuss the neurobiology, cognitive factors, and major computational theories, and revisit the predominant view that extinction results in new learning that interferes with expression of the original memory. Additionally, we reconsider the limitations of extinction as a technique to prevent the relapse of maladaptive behavior and discuss novel approaches, informed by contemporary theoretical advances, that augment traditional extinction methods to target and potentially alter maladaptive memories.